Evaluation of sight distance at an intersection with stop sign control - Hamiza, Mohamad Salleh. (UNIMAS, 2006)
A primary feature in highway design is the arrangement of the geometric elements so that sufficient sight distance is provided for safe and efficient operation. This can be achieved by installing traffic control devices which have an important role in highway design and it can control vehicles movement on highway.This projectis about an evaluation of sight distance at an intersection with stop sign control.Therefore, the performance of sight distance at an intersection will be examined. A method from American Association of State Highway and Transportation Officials (AASHTO) is used to evaluate the recommended intersection sight distance. Experiments were done at four intersections which have T-intersection with stop sign control. Those intersectionsare:Jalan Muda Hashim intersection, Jalan Rubber intersection, Jalan Perimat intersection and Jalan Bayor Bukit intersection.Consequently, the data from the experiments are analysed and then compared with there commended intersection sight distance. If the existing sight distance is less than the recommended sight distance, some suggestions are proposed to mitigate the problem.It was found that sight distance at Jalan Muda Hashim intersection and Jalan Rubber intersection are adequate while sight distance at Jalan Perimat intersection and Jalan Bayor Bukit intersection are inadequate. Therefore, some suggestions are recommendedto mitigatethe problem.